PROBLEMS OF THE PROCESS, THE EFFECT OF THE INTENSITY AND TIME OF MIXING ON THE EFFECT OF MIXING REAGENTS WITH WATER - Mirzaev Abdialim (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article presents the research results and provides information on the types of reagents, types of mechanical mixers and the main tasks of the process of mixing natural turbid waters with reagents